Risk assessment, modeling and decision support strategic directions - Bostrom, Ann. (Risk, Governance and Society ;)
A brief history of seismic risk assessment - Perspectives on the history of seismic risk assessment - Strategic directions in seismic modeling: Hazus® development and current applications for catastrophe planning - Perspectives on development and current applications for catastrophe planning - Loss estimation models and metrics - Perspectives on loss estimation models and metrics - Seismic risk mitigation decisions under uncertainty - Perspectives on seismic risk mitigation decisions under uncertainty - Modeling seismic mitigation strategies - Perspectives on modeling seismic mitigation strategies - Visualizing uncertainty in natural hazards - Perspectives on visualizing uncertainty in natural hazards - Conclusion.